2017
DOI: 10.5811/cpcem.2016.11.32294
|View full text |Cite
|
Sign up to set email alerts
|

Pasteurella multocida Epiglottitis

Abstract: Epiglottitis is an uncommon but life-threatening disease. While the most common infectious causes are the typical respiratory pathogens, Pasteurella multocida is a rare causative organism. We present a case of P. multocida epiglottitis diagnosed by blood culture. The patient required intubation but was successfully treated medically. P. multocida is a rare cause of epiglottitis; this is the ninth reported case in the literature. Most diagnoses are made from blood culture and patients usually have an exposure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Only nine other cases of epiglottitis in the literature have been attributed to P. multocida (Table 1). [2][3][4]6,[8][9][10][11][12] To our knowledge, this represents the 10th case. Infection in all but one of the 10 cases was related to animal exposure-primarily cats, but dogs have been implicated as well.…”
Section: Discussionmentioning
confidence: 73%
“…Only nine other cases of epiglottitis in the literature have been attributed to P. multocida (Table 1). [2][3][4]6,[8][9][10][11][12] To our knowledge, this represents the 10th case. Infection in all but one of the 10 cases was related to animal exposure-primarily cats, but dogs have been implicated as well.…”
Section: Discussionmentioning
confidence: 73%
“…This result surpassed that of Khamesipour et al [ 24 ] from Iran, who recovered P. multocida from 11.4% of pneumonic cases and 4.4% of healthy cases. The isolation of P. multocida from cases of human epiglottitis was confirmed by Glickman and Klein [ 25 ] from the USA, who demonstrated its presence in adults without exposure to animals, and Moyko and Ali [ 26 ], who confirmed epiglottitis in a human who was exposed to animals. As the human samples were collected from animal owners and farm workers, this could suggest that exposure to animals can enhance infection transmission to humans.…”
Section: Discussionmentioning
confidence: 92%
“…The high resistance in the P. multocida isolates to cefotaxime contradicts the results of Elshemey et al [ 39 ] from Egypt, who confirmed that cefotaxime was the most effective antimicrobial against P. multocida , accompanying the foot and mouth disease virus SAT 2 FMD on bovine farms in Alexandria province, Egypt. Scarce data were found concerning the antimicrobial susceptibility profiles of P. multocida isolated from human epiglottitis, although Glickman and Klein [ 25 ] confirmed that an isolate from an infected 44-year-old human patient from the USA was susceptible to ceftriaxone, and Moyko and Ali [ 26 ] showed that an isolate from a 49-year-old female from the USA was susceptible to ampicillin–sulbactam.…”
Section: Discussionmentioning
confidence: 99%
“…Fewer than 20 cases of P. multocida epiglottitis have been reported in the literature; all of which occurred in middle-aged adults. 7,9 Epiglottitis due to P. multocida has previously been described in nonbite transmissions. 9 Pasteurella multocida can also manifest as bacteremia.…”
Section: Discussionmentioning
confidence: 99%
“…Epiglottitis is described as inflammation of the epiglottis and surrounding tissue. It is most commonly caused by group A β-hemolytic Streptococcus pneumoniae , Staphylococcus aureus , or Haemophilus influenzae (type B, A, F, and nontypable) 7,9 . It has been hypothesized that the mortality rate in adult epiglottitis is higher than that of children because adult epiglottitis is often not diagnosed in a timely manner 9 .…”
Section: Discussionmentioning
confidence: 99%